Enhancing sugarcane’s drought resilience: the influence of Streptomycetales and Rhizobiales - Chen, Mianhe; Xing, Yuanjun; Chen, Chunyi; Wang, Ziting (Frontiers in Plant Science, 2024)
Drought stress is a critical environmental factor affecting sugarcane yield, and adaptability of the sugarcane rhizosphere bacterial community is essential for drought tolerance. This review examines the adaptive responses of sugarcane rhizosphere bacterial communities to water stress and explores their significant role in enhancing sugarcane drought tolerance. Under drought conditions, the sugarcane rhizosphere bacterial community undergoes structural and functional shifts, particularly the enrichment of beneficial bacteria, including Streptomycetales and Rhizobiales. These bacteria enhance sugarcane resilience to drought through various means, including nutrient acquisition and phytohormone synthesis. Furthermore, changes in the rhizosphere bacterial community were closely associated with the composition and levels of soil metabolites, which significantly influenced the physiological and biochemical processes of sugarcane during drought stress. This study deepens our understanding of rhizosphere bacterial communities and their interactions with sugarcane, laying a scientific foundation for developing resistant sugarcane varieties, optimizing agricultural practices, and opening new avenues for agricultural applications.